Econstruct a feasibility study on the use of phase change materials on construction materials - Bautista, Karissa May B.; Daway, Gerrick Junn C.; Domingo, Cecilia Leonida N.; Perez, Jose Alvin S. (Quezon City College of Engineering, University of the Philippines Diliman, 2010)
The project explores the feasibility of establishing a company that has the goal of manufacturing and distributing environmental-friendly construction materials. In conjunction to this, the project also studies the feasibility of the development, launch and production of the company's first product brand: Fricpaint, which is essentially a temperature regulating exterior paint. Friopaint regulates the temperature of house interiors by the use of the developing Phase Change Material (PCM) technology which makes use of materials that change phase (melts or solidifies) in room temperature.The PCM consumes the physical, sensible heat from the environment and turns it into latent heat which is the energy used to change phases. The production of Friopaint requires these materials to be inserted into thermally conductive microcapsules so that the product can maintain its structure and stability even when undergoing phase changes. The feasibility study was composed of five steps that comprehensively study different aspects of the project.These aspects are the marketing, technical, organizational, financial and social profitability parts of the project. For the marketing aspect target market was identified. The study considered two consumer segments were initially identified; rational, which consisted of development corporations and the emotional customers which were the families and the heads of houses. First and second degree information were gathered through the use of consumer surveys as well as interviews through established paint companies and chemical research companies such as Pacific Paints (Boysen) Inc. and ADD Paint Research Inc. Through the primary data research,it was determined that market acceptance has high potential. The market was then segmented into two further classifications for the emotional segment; the above 35 years of age and the 35 years of age and below. Subsequent strategies for each of the segments were then identified and a suitable marketing mix was developed. Based from the determined market size and the estimated market share, revenues for the first five years were also computed. The technical feasibility was then studied by researching on the raw materials and plant equipment needed for production. Suppliers of these materials were found both locally and internationally. The manufacturing plant is to be located in a TechnoPark in Laguna since tax exemptions for such industries are available in this area. The layout of the building was also constructed to be as suitable to the manufacturing processes. Costs for all these expenses were computed. An organizational structure was created to determine the necessary labor force for production and to assign job positions. Employee salary rates and benefits were specified depending on the financial capability of the company. To consolidate the projected revenues and the estimated costs, a financial study was done by generating financial statements and analyses. Projected income statements, cash flow statements, and balance sheets for the first five years were made. It was determined that there will be initial losses in during the first two years until income is finally generated in the third year.
Submitted in partial fulfillment of the course requirements in IE 153 : Project development and management.
Keywords: Paint industry and trade -- Philippines; Feasibility studies